THE INFLUENCE OF RESTAURANT AMBIENCE AND SERVICE QUALITY ON CUSTOMER SATISFACTION AT PONDOK HIJAU RESTAURANT MANADO - Senduk, Dylan C. (Jurnal Berkala Ilmiah Efisiensi, 2016)
Food is one of the basic human needs. The fulfillment of food becomes absolute if people want to remain able to maintain the continuity of their life. The market of food has always played a central role in human's life, communities, communication, and culture. Restaurant is a business which prepares and serves food and drinks to customers in exchange for money, either paid before the meal or after the meal. Restaurants vary greatly in appearance and offerings, including a wide variety of cuisines and service models starting from inexpensive fast food restaurants to high-priced luxury establishment. This research is aimed to know the influence of Restaurant Ambience and Service Quality on Customer Satisfaction by applying Multiple Regression Analysis. This method is to enable understanding the relationship between the Restaurant Ambience and Service Quality to the Customer Satisfaction.